Peripheries Are Supposed to Quote - Szwabowski, Oskar; Zańko, Piotr (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This is an angry punk collective autoethnography – we scream about inequalities in knowledge production.This is an angry punk collective autoethnography – we scream about our experience of being rejected by so-called international journals.This is an angry punk collective autoethnography – we scream in Polish and English according to the margin lever.This is an angry punk collective autoethnography – we scream from the semi-periphery. We’re really screwed!